Using contingent valuation method in estimating the public benefits of the Marikina City Library - Necesario, Roy Santos S. (2015)
Public libraries have been constantly finding themselves at a critical standpoint in which they need to prove their economic relevance and worth to their respective contiguous communities. This study employs the contingent valuation method as an economic valuation tool to help justify the continued financial funding of Marikina City Library. The method relies on direct valuation, which involves creating hypothetical scenarios and asking survey respondents to state their 1) willingness and ability to pay (WTP) for a good or service for the hypothetical removal of a service and subsequent offering of it in an open market and 2) willingness to accept (WTA) compensation of invested money in taxation for the removal of the service altogether. The residents of Marikina were divided into users and non-users, defined as those that have not used the library and its programs and services in the past 12 months. Their answers on the survey were also analysed and correlated based on their socio-economic backgrounds of highest educational attainment, income status, and annual family income. In order to remove response bias, the questionnaire handed out were divided into one that informs respondents of the actual tax value they pay for the programs and services of the library, called as the baseline value, and one that does not present such value.